SDSS-IV MaNGA: the spatial distribution of star formation and its dependence on mass, structure, and environment. Issue 1 (31st January 2018) - Spindler, Ashley; Wake, David; Belfiore, Francesco; Bershady, Matthew; Bundy, Kevin; Drory, Niv; Masters, Karen; Thomas, Daniel; Westfall, Kyle; Wild, Vivienne
Abstract: We study the spatially resolved star formation of 1494 galaxies in the SDSS-IV MaNGA Survey. Star formation rates (SFRs) are calculated using a two-step process, using H α in star-forming regions and Dn 4000 in regions identified as active galactic nucleus/low-ionization (nuclear) emission region [AGN/LI(N)ER] or lineless. The roles of secular and environmental quenching processes are investigated by studying the dependence of the radial profiles of specific star formation rate on stellar mass, galaxy structure, and environment. We report on the existence of 'centrally suppressed' galaxies, which have suppressed Specific Star Formation Rate (SSFR) in their cores compared to their discs. The profiles of centrally suppressed and unsuppressed galaxies are distributed in a bimodal way. Galaxies with high stellar mass and core velocity dispersion are found to be much more likely to be centrally suppressed than low-mass galaxies, and we show that this is related to morphology and the presence of AGN/LI(N)ER like emission. Centrally suppressed galaxies also display lower star formation at all radii compared to unsuppressed galaxies. The profiles of central and satellite galaxies are also compared, and we find that satellite galaxies experience lower specific star formation rates at all radii than central galaxies. This uniform suppression could be a signal of the stripping of hot halo gas in the process known as strangulation. We find that satellites are not more likely to be suppressed in their cores than centrals, indicating that the core suppression is an entirely internal process. We find no correlation between the local environment density and the profiles of star formation rate surface density.